2018
DOI: 10.1080/2162402x.2017.1373233
|View full text |Cite
|
Sign up to set email alerts
|

Biglycan-mediated upregulation of MHC class I expression in HER-2/neu-transformed cells

Abstract: The extracellular matrix protein biglycan (BGN) has oncogenic or tumor suppressive potential depending on the cellular origin. HER-2/neu overexpression in murine fibroblasts and human model systems is inversely correlated with BGN expression. Upon its restoration BGN HER-2/neu fibroblasts were less tumorigenic in immune competent mice when compared to BGN HER-2/neu cells, which was associated with enhanced immune cell responses and higher frequencies of immune effector cells in tumors and peripheral blood. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 61 publications
1
23
0
Order By: Relevance
“…Proteoglycans did not show a statistically significant anti-proliferative effect in isolated PDX-derived lymphoma cells. Although there was no evidence of direct incorporation of the administered proteoglycans into the PDTX ECM, BGN administration resulted, as previously described (44), in 20% increase in DCN content (p = 0.032, vs. vehicle) in the PDTX2 ECM. Overall, this suggest that the anti-proliferative effect of these proteoglycans results from both short-and longrange interactions.…”
Section: Lme Heterogeneity Decreases With Disease Progressionsupporting
confidence: 71%
“…Proteoglycans did not show a statistically significant anti-proliferative effect in isolated PDX-derived lymphoma cells. Although there was no evidence of direct incorporation of the administered proteoglycans into the PDTX ECM, BGN administration resulted, as previously described (44), in 20% increase in DCN content (p = 0.032, vs. vehicle) in the PDTX2 ECM. Overall, this suggest that the anti-proliferative effect of these proteoglycans results from both short-and longrange interactions.…”
Section: Lme Heterogeneity Decreases With Disease Progressionsupporting
confidence: 71%
“…BGN is modulated by and can modulate the TGF-β pathway by regulating the expression/activity of SMAD family members. 3 TGF-β treatment of the murine in vitro models and human BC cell lines caused a significantly enhanced miR-21-3p expression in BGN low HER-2/neu + cells, a heterogeneous increase in BC cell lines, but only a marginal upregulation in BGN high HER-2/neucells ( Figure S2). SMAD2 expression is downregulated in BGN low HER-2/neu + cells, but significantly enhanced in BGN-transfected HER-2/neu + cells (Figure 2A).…”
Section: Identification Of a Novel Mir-21-3p/tgf-β Signaling-driven Imentioning
confidence: 99%
“…1,2 Recently, we have shown that HER-2/neu transformation resulted in a downregulation of BGN, causing a reduced MHC class I surface expression. 3 However, a relationship between miR-21-3p overexpression, enhanced TGF-β signaling, impaired BGN, and MHC class I expression in HER-2/neu + cells has not yet been investigated.…”
Section: Identification Of a Novel Mir-21-3p/tgf-β Signaling-driven Imentioning
confidence: 99%
“…Emerging evidence suggests key roles of tumor extracellular matrix (ECM) components and their proteolytic remodeling products in regulating the cancer-immunity cycle [103]. Indeed, the small leucine rich proteoglycan family member biglycan (BGN) has recently been associated with an altered MHC class I expression [104]. BGN expression could be downregulated by oncogenic transformation [105].…”
Section: Modulating Resistance Mechanisms Underlying T Cell-based Immunotherapymentioning
confidence: 99%